Islam and rationality : the impact of al-Ghazali : papers collected on his 900th anniversary - Tamer, Georges.; Griffel, Frank, 1965- (Islamic Philosophy, Theology and Science. Texts and Studies, 2015)
This volume offers an account of Abū Ḥāmid al-Ghazālī (d. 505/1111) as a rational theologian who created a symbiosis of philosophy and theology and infused rationality into Sufism. The majority of the papers herein deal with important topics of al-Ghazālī's work, which demonstrate his rational treatment of the Qurʾān and major subjects of Islamic theology and everyday life of Muslims. Some other contributions address al-Ghazālī's sources and how his intellectual endeavors were later received by scholars who had the same concern of reconciling religion and rationality within Islam, Christianity and Judaism. With contributions by Binyamin Abrahamov, Hans Daiber, Ken Garden, Avner Giladi, Scott Girdner, Frank Griffel, Steven Harvey, Alfred Ivry, Jules Janssens, Taneli Kukkonen, Luis Xavier López-Farjeat, Wilferd Madelung, Yahya M. Michot, Yasien Mohamed, Eric Ormsby, M. Sait Özervarlı, and Hidemi Takahashi.